Предмет: Алгебра, автор: Нелианна

помогите пожалуйста.
1)(x+1)(x+2)(x+3) / (2x-1)(x+4)(3-x) >0

2) x^2-4x-2 / 9-x^2 <0

3) 1 /x+1 + 2 / x+3 > 3 / x+2

4) 1 / x < 1 / 3

5) 1 / x+1 - 2 / x^2-x+1 <(или равно)  1-2x / x^3+1 .

Ответы

Автор ответа: eugeke
0
#1

 frac{(x+1)(x+2)(x+3)}{(2x-1)(x+4)(3-x)}&gt;0

x+1=0
x=-1

x+2=0
x=-2

x+3=0
x=-3

2x-1neq0
xneq frac{1}{2}

x+4neq0
xneq-4

3-xneq0
xneq3

Ответ: xin (-4;-3) U (-2;-1) U( frac{1}{2}; 3)

#2

 frac{x^2-4x-2}{9-x^2}&lt;0

x^2-4x-2=0
D=16+8=24;  sqrt{D}=2 sqrt{6}
x_{1/2}= frac{4pm2 sqrt{6} }{2}= frac{2(2pm sqrt{6}) }{2}=2pm sqrt{6}

9-x^2neq0
x^2neq9
xneq pm3

Ответ: xin (-infty; -3)U(2-sqrt{6};3)U(2+sqrt6; +infty)

#3

 frac{1}{x+1}+ frac{1}{x+3}&gt; frac{3}{x+2}

 frac{1}{x+1}+ frac{2}{x+3}- frac{3}{x+2}&gt;0

 frac{x^2+3x+2x+6+2(x^2+x+2x+2-[3(x^2+x+3x+3)]}{(x+1)(x+2)(x+3)}&gt;0

 frac{x-1}{(x+1)(x+3)(x+2)}&lt;0

x-1=0
x=1

x+1neq0
xneq-1

x+2neq0
xneq-2

x+3neq0
xneq-3

Ответ: xin (-3;-2)U(-1;1)

#4

 frac{1}{x}&lt; frac{1}{3}

 frac{1}{x}-  frac{1}{3}&lt;0

 frac{3-x}{3x}&lt;0

3-x=0
x=3

3xneq0
xneq0

Ответ: xin (-infty; 0)U(3;+infty)

Похожие вопросы
Предмет: Қазақ тiлi, автор: aselbutabaeva34
Предмет: Математика, автор: salihovaanel57